2020
DOI: 10.1038/s41467-020-16249-x
|View full text |Cite
|
Sign up to set email alerts
|

A redox-based electrogenetic CRISPR system to connect with and control biological information networks

Abstract: Electronic information can be transmitted to cells directly from microelectronics via electrode-activated redox mediators. These transmissions are decoded by redox-responsive promoters which enable user-specified control over biological function. Here, we build on this redox communication modality by establishing an electronic eCRISPR conduit of information exchange. This system acts as a biological signal processor, amplifying signal reception and filtering biological noise. We electronically amplify bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 72 publications
1
50
0
Order By: Relevance
“…Further, we envision that redox‐linked bioelectronics will enable new approaches for coupling biology (e.g., synthetic biology) to electronics to enhance information processing for the sensing and actuation of biological systems. [ 31,75–77 ] Finally, we suggest that catechols could emerge as important molecular circuit elements for miniaturize‐able, deployable and sustainable systems for redox‐linked bioelectronics. [ 78–84 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we envision that redox‐linked bioelectronics will enable new approaches for coupling biology (e.g., synthetic biology) to electronics to enhance information processing for the sensing and actuation of biological systems. [ 31,75–77 ] Finally, we suggest that catechols could emerge as important molecular circuit elements for miniaturize‐able, deployable and sustainable systems for redox‐linked bioelectronics. [ 78–84 ]…”
Section: Discussionmentioning
confidence: 99%
“…We are investigating the use of redox as a modality for bioelectronic communication [ 2,30,31 ] and have previously shown that the coating of electrodes with catechol‐based hydrogel films confers important molecular electronic properties for amplifying, rectifying, and gating redox‐based electrical currents. [ 15,17,32–35 ] Here, we extended a simple electrofabrication method [ 36–42 ] to pattern catechols onto a flexible hydrogel film, and developed a network model to analyze the redox‐based electron flow through this patterned region.…”
Section: Introductionmentioning
confidence: 99%
“…By integrating CRISPR with electronics they showed that spatiotemporal redox commands generated upon electrical stimulation can be processed and decoded by gelatin‐encapsulated E. coli . This way of establishing the redox communication channels provides the capability to electrically modulate gene expression and cell behavior (Bhokisham et al, 2020). This further opens the opportunities to develop nanoscale systems for modulation of redox processes that can be applied to actuate behavior of complex eukaryotic cell.…”
Section: Wireless Nanobioelectronic Toolsmentioning
confidence: 99%
“…For instance, Stanley et al developed a system for magnetically triggered release of insulin from mammalian cells ( Stanley et al, 2015 ). We introduced electronic control of target gene expression by tapping into the switchable oxidation state of native redox active molecules ( Tschirhart et al, 2017 ; Bhokisham et al, 2020 ). This allowed electronic access to an array of biological molecules or functions that can be synthesized or carried out by cells.…”
Section: Introductionmentioning
confidence: 99%